SUMBER BELAJAR BERBASIS KOMPUTER DAN PENERAPANNYA DI SEKOLAH DASAR - I Wayan Karmana (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2010)
Abstract: There is a variety of learning resources. One of the variety of learning resources is learning resource based on computer which has very fast development in education world,  i.e.formal, informal, and non formal education.The use of this resources can be seen as as a compulsory in education world in 21st century and it is very appropriate for elementary schools' students because it has learning, playing, and  early IT introduction dimensions.   In application it can be seen in computer assisted instructional with program: tutorial, drills and practice, simulation and instructional game, eventually developed on multimedia teaching, includes internet. The resource has a big enough contribution so teaching became more effective and eficient. Existence of the resources was not for replacing teachers' role but as an alternative learning resources in  the  knowledge age. Even though there are side effects, the implementation of the resource can be solved and it is our responsibility for making the effects minimum dan solved.   Abstrak: Sumber belajar (learning resources) banyak jenisnya. Salah satunya adalah sumber belajar (media) berbasis komputer yang saat ini sangat pesat perkembangannya dalam dunia pendidikan baik formal, informal maupun non formal. Penggunaan sumber ini sudah menjadi tuntutan dunia pendidikan abad 21 yang bersifat global dan sangat cocok untuk siswa SD karena memiliki dimensi belajar, bermain, dan pengenalan TI secara dini. Dalam aplikasinya berupa pembelajaran dengan bantuan komputer (Computer Assisted InstructionI) dengan program berbentuk: tutorial, drills and practice (latihan), simulasi dan permainan instruksional, selanjutnya berkembang ke pembelajaran multimedia termasuk internet. Kontribusinya cukup besar sehingga pembelajaran dapat lebih efektif dan efisien, namun bukan untuk menggantikan peran guru , tetapi sebagai salah satu alternatif sumber belajar di abad pengetahuan (knowledge age). Walaupun disisi lain ada dampak negatifnya, itu dapat disiasati serta menjadi tanggung jawab kita semua untuk meminimalisir dan mengatasinya.